The tenement homes of Dublin: their condition and regulation - Eason, Charles (Statistical and Social Inquiry Society of Ireland, 1899)
The condition of the tenement houses of Dublin was enquired into by the Royal Commission upon the Sewerage and Drainage of Dublin in 1879. Their report states that "9,760 houses were occupied as dwellings let in tenements," and that of these 2,300, occupied by about 30,000 persons, were in a condition unfit for habitation. The report recommends the gradual closing of the ruinous houses, and the supervision and daily regulation of the others, and it also says that by the provision of improved sanitary accommodation, and the strict enforcement of the provisions of the Public Health Act against overcrowding, a considerable proportion of the tenement houses can be converted into healthy dwellings. The report pointed out that it is the duty of the Corporation to determine how many persons are to be allowed to occupy each room, and to ascertain, by frequent inspection, that the number fixed upon be not exceeded. The Commissioners affirmed "that the tenement houses of Dublin appear to be the prime source and cause of the excessively high death rate; that they are not properly classified, registered, and regulated ; that they are dilapidated, dirty, ill-ventilated, much overcrowded, and that disease, a craving for stimulants and its consequences?drunkenness and extreme poverty, are thereby fostered, and that until the condition of these houses shall have been improved the general health of the city will continue to be injuriously affected."
Read Tuesday, 13th December, 189S
Keywords: Dublin tenements; Living standards; 314.15